Recent advances and future challenges of nano-based drug delivery systems - Jahan, Nazish; Huda, Noor Ul; Fatima, Arooj; Shamshad, Huma (Nano and Medical Materials, 2023)
Nanomedicine and nano-delivery systems constitute an emerging and swiftly progressing discipline, employing nanoscale materials for diagnostic tools and targeted, controlled administration of therapeutic agents. Nanotechnology offers substantial advantages for treating chronic ailments, facilitating precise, site-specific delivery of therapeutic agents. Recent applications encompass a diverse array of nanomedicine implementations, including chemotherapeutic, biological, and immunotherapeutic agents, for treating diverse medical conditions. This comprehensive review provides an updated summary of recent strides in the realm of nanomedicines and nano-based drug delivery systems. It critically examines the utilization of nanomaterials to enhance the effectiveness of both novel and established drugs (e.g., natural products) and to enable selective disease diagnosis through the identification of disease marker molecules. The review also addresses the prospects and challenges associated with the transition of nanomedicines from synthetic or natural origins to their practical clinical deployment. Furthermore, the document offers insights into prevailing trends and future prospects within the domain of nanomedicine.